2021
DOI: 10.1177/01650254211053054
|View full text |Cite
|
Sign up to set email alerts
|

Can language modulate perceptual narrowing for faces? Other-race face recognition in infants is modulated by language experience

Abstract: Between 6 and 9 months, while infant’s ability to discriminate faces within their own racial group is maintained, discrimination of faces within other-race groups declines to a point where 9-month-old infants fail to discriminate other-race faces. Such face perception narrowing can be overcome in various ways at 9 or 12 months of age, such as presenting faces with emotional expressions. Can language itself modulate face narrowing? Many adult studies suggest that language has an impact on the recognition of ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 66 publications
0
8
2
Order By: Relevance
“…However, if they have similar language-processing mechanisms to adults from infancy, it would be interesting in future studies to add oculometric or pupil measurements to confirm or not whether, in the case of abstract pattern memorization, similar mechanisms could justify our behavioral observations. Furthermore, contrary to our findings, in which native language does not seem to hinder the recognition of unfamiliar abstract patterns, Clerc et al (2022) have shown that the presence of a native language hinders the recognition of unfamiliar faces. Infants are initially able to recognize individuals from any type of own-race and other-race faces.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, if they have similar language-processing mechanisms to adults from infancy, it would be interesting in future studies to add oculometric or pupil measurements to confirm or not whether, in the case of abstract pattern memorization, similar mechanisms could justify our behavioral observations. Furthermore, contrary to our findings, in which native language does not seem to hinder the recognition of unfamiliar abstract patterns, Clerc et al (2022) have shown that the presence of a native language hinders the recognition of unfamiliar faces. Infants are initially able to recognize individuals from any type of own-race and other-race faces.…”
Section: Discussioncontrasting
confidence: 99%
“…Our sample size was based on the study by Hillairet de Boisferon et al (2021), Experiment 2, and Clerc et al (2022) where they tested about forty 12-month-olds in a VPC. All participants were healthy full-term infants raised in monolingual French environment, recruited via their parents, at the maternity ward of the Grenoble University Hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The present study provides further evidence of strong interactions between face and speech processing during early child development. Previous studies have already demonstrated that face and speech processing specialize at a similar time and that they interact with each other (Clerc et al., 2022; Hillairet de Boisferon et al., 2021; Krasotkina et al., 2021). However, our study shows for the first time that those interactions also influence the social learning behavior in further child development.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, we used videos of talking faces instead of static pictures as stimuli, a setup closer to infants' everyday life. In contrast, previous studies often used static pictures (e.g., Clerc et al, 2022) instead of videos.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…It would be worthwhile to examine how race–language associations are learned earlier in life from a developmental perspective. Based on the influence of speaker race on language comprehension (Singh et al, 2020), word processing (Weatherhead & White, 2018), and language-oriented face recognition (Clerc et al, 2022), it is possible that a younger population may show a similar pattern of learning in a study like the present.…”
Section: Limitations and Future Directionsmentioning
confidence: 96%